Early generation selection strategy for yield and yield components in white oat (Scientia Agricola, 2005)
Several studies have searched for higher efficiency on plant selection in generations bearing high frequency of heterozygotes. This work aims to compare the response of direct selection for grain yield, indirect selection through average grain weight and combined selection for higher yield potential and average grain weight of oat plants (Avena sativa L.), using the honeycomb breeding method. These strategies were applied in the growing seasons of 2001 and 2002 in F3 and F4 populations, respectively, in the crosses UPF 18 CTC 5, OR 2 ;´; UPF 7 and OR 2 ;´; UPF 18. The ten best genetic combinations obtained for each cross and selection strategy were evaluated in greenhouse yield trials. Selection of plants with higher yield and average grain weight might be performed on early generations with high levels of heterozygosis. The direct selection for grain yield and indirect selection for average grain weight enabled to increase the average of characters under selection. However, genotypes obtained through direct selection presented lower average grain weight and those obtained through the indirect selection presented lower yield potential. Selection strategies must be run simultaneously to combine in only one genotype high yield potential and large grain weight, enabling maximum genetic gain for both characters.